The insult [videorecording (DVD)] - Karam, Adel; Bāshā, Kāmil; Salameh, Camille (Entertainment One Film USA, 2018)
After an emotional exchange between a Lebanese Christian and a Palestinian refugee escalates, the men end up in a court case that gets national attention.